functions dpp key
functions dpp key
functions dpp key
MATHS :-
61) 1 62) 1 63) 3 64) 2 65) 1 66) 4 67) 4 68) 4 69) 1 70) 1
71) 3 72) 4 73) 4 74) 4 75) 4 76) 1 77) 4 78) 4 79) 1 80) 1
81) 4 82) 2 83) 4 84) 1 85) 3 86) 3 87) 3 88) 2 89) 1 90) 3
MATHS
ax + b
1. f ( x) =
cx + d
ax + b
a +b a 2 x + ab + bcx + bd
cx + d
fof ( x ) = fof ( x ) =
ax + b acx + bc + cdx + d 2
c +d
cx + d
fof ( x ) =
(a 2
+ bc ) x + ( ab + bd )
=x
( ac + cd ) x + ( bc + d 2 )
a 2 + bc = bc + d 2 a = d or a = −d
and ab + bd = 0 b = 0 or a = −d
and ac + cd = 0 c = 0 or a = −d
2. Option 2 is f ( x )
Option 4 is f ( x )
3. g ( x1 ) = g ( x2 ) x1 = x2
f g ( x1 ) = f ( g ( x2 ) ) x1 = x2
Page 1
one − one
4. − x = − x − 1 if xI
Hence f ( − x ) = − f ( x )
5. x + b − x + b = x + b period '1'
a − b constant
Always periodic
7. Conceptual
8. f ( x2 ) = x2 −1
( f ( x ) ) = ( x − 1)
2 2
f ( x ) = x −1
f ( x) = f ( x)
5 2
9. Put x = and
6 3
1 3 1
2 f + 2 f = …..(1)
2 2 3
3 1
2 f + 2 f = 3 ……(2)
2 2
By (2) - 2 (1)
1 2 −3
f =
2 6
Page 2
2a 2 − a 0 a ( 2a − 1) 0
1
a ( −, 0 ,
2
Let g ( x ) x 2 + ( a + 1) x + ( a − 1) = 0
i) D 0
( a + 1) − 4 ( a − 1) 0 a R …..(i)
2
B
ii) −2 − 1
2A
−2 −
( a + 1) 1
2
a ( −3, 3) …..(ii)
iii) g ( −2 ) 0
4 − 2 ( a + 1) + ( a − 1) 0 a 1
iv) g (1) 0
1 + a + 1 + a − 1 0
1
a −
2
1 1
a − , 0 , 1
2 2
1
12. f ( x) = + 1 − x − 1
2 − x
1
= + − x − 1 2 − 1 (Using A.M . G.M . )
2 − x
Range of f ( x ) is 2 − 1, )
Page 3
1 + x3
14. f ( x ) = sin 3/2 + sin ( sin x ) + log 3x+1 ( x 2 + 1)
−1
2x ( )
Domain : 3 x + 1 1or 0 x I
1 + x3
And −1 3/2 1
2x
−2 x3/2 1 + x3 2 x3/2
1 + x3 + 2 x3/2 0
(1 + x )
3/2 2
0 xR
Hence domain x
x 2 − 4 x + 3 = 0 ( x − 2 ) − 1 −1
2
15.
3
0,
4
16. (i) f ( x ) = x − 1 + 2 3 − x
D : x − 1 0 &3 − x 0 x 1, 3
1 1
Range : f ' ( x ) = − =0
2 x −1 3− x
7
or f ' ( x ) = 0 at x =
5
7− 7+
f ' 0 & f ' 0
5 5
7
maxima at x =
5
Range : 2, 10
Page 4
sin x = −1, 0,1
In this case
2 cos x = −2
sin x = −1
18. x3 0 & x 2 0 x 0
19. ( 3 x − 1) ( 2 x − 1) 0
1 1
x
3 2
20. f ( xy + 1) = f ( yx + 1)
f ( x) f ( y) − f ( y) − x + 2 = f ( y ) f ( x) − f ( x) − y + 2
f ( x) − f ( y) = x − y
Putting y = 0
f ( x ) −1 = x − 0
f ( x) = x +1
21. f (−x) = f ( x)
a− x −1 ax −1
=
(−x) (a −x
+ 1) x n ( a x + 1)
n
22. f ( x ) = ax 2 + bx + c
f ( 0) = c c I
f (1) = a + b + c ( a + b + c ) I
Page 5
1 1 2 1
25. f x + = x + + x + + x + 1 − 3 x + + 15
3 3 3 3
1 2
= x + + x + + x − 3x + 15 = f ( x )
3 3
x x
26. 2 x 4 1 2 = 1
2 2
f ( x ) = x −1
f −1 ( x ) = x + 1 : (1,3) → ( 2, 4 )
f(x) = 2x
f(5) = 12
30. 3 £ [ x] £ 2 Þ - 2 £ [ x] £ 2 Þ - 2 £ x < 3
Page 6